Predicting Factors of Breast Self-Examination based on Health Belief Model and Locus of Control among Women Aged 20-50 Years - Afsaneh Sahraee; Azita Noroozi; Rahim Tahmasebi (Tehran University of Medical Sciences, 2013)
Background & Aim: Although breast self-examination (BSE) is no longer recommended for screening of breast cancer, its training and practicing is a gateway to health promotion and provides women with knowledge and attitudes that set the stage for clinical breast examination and mammography screening later in life. The aim of this study was to recognize predicting factors of the BSE based on the Health Belief Model (HBM) and the locus of control model among women aged 20-50 years old.   Methods & Materials : Inthis cross-sectional study,400 women were selected through theconvenience sampling method from health centers. Data were collected using four questionnaires including the Champion's Scale, health locus of control, and demographic and functional questionnaires. Data were analyzed in the SPSS using independent T-test, Chi-squared test, logistic and linear regression models.   Results: The results showed that 10.9% of the participants reported performing BSE regularly. Perceived self-efficacy was the strongest positive predictor in the BSE performance (Exp (B) =1.863). Awareness had direct and indirect effects on the BSE. The locus of control did not predict the BSE (p=0.05).   Conclusion : Improving self-efficacy, especially in young women, and increasing awareness about cancer among women is necessary to increase the rate of the BSE.